Investigating the key influencing factors of pre-jump height in juvenile trampoline gymnasts using grey relational analysis - Wang, Hui; Zhang, Su; Dai, Hanya; Gong, Mingxin; Zou, Ningxiang; Jia, Feng; Wang, Lejun (Frontiers in Psychology, 2025)
ObjectiveAchieving greater pre-jump elevation is essential for trampoline gymnasts to attain high-level competition performance. This study aimed to explore the key influencing factors of pre-jump height in juvenile trampoline gymnasts, thereby providing a rationale for training programs and talent selection criteria.MethodsA mixed-methods approach was adopted. First, a comprehensive literature review, expert interviews, and theoretical analysis were conducted to establish preliminary indicators potentially influencing pre-jump height. Second, experimental tests were carried out on 16 juvenile trampoline gymnasts to collect data on these indicators. Third, factor analysis was applied to refine the initial indicator system and develop a formal evaluation framework. Finally, grey relational analysis was used to quantify the relationships between each indicator and pre-jump height.ResultsThe final indicator system encompassed 5 dimensions and 16 representative variables. The grey relational analysis revealed that 10 indicators—standing long jump, height, leg length, shoulder width, arm hang angle, ratio of counter-jump height to pre-jump height, 30-s hanging leg raise, BMI, hip joint angle at landing, and state anxiety level—showed strong correlations (grey relational coefficient > 0.9) with pre-jump height. Furthermore, three additional indicators—trampoline-induced acrophobia, daily acrophobia, and ankle joint cushioning—demonstrated moderate correlations (coefficient 0.8–0.9). In contrast, time perception (10 s), supine leg raise (45°), and self-rotation perception showed weaker correlations (coefficient < 0.8).ConclusionThis study established an indicator system consisting of 16 items of pre-jump height influencing factors and identified the importance ranking of each indicator using grey relational analysis in juvenile trampoline gymnasts. These findings may serve as a scientific basis for developing targeted training programs and objective talent selection criteria while advancing gymnastics research by highlighting the interaction of physical, technical, and psychological factors in specialized jumping performance.